Process Equipment Failure Mode Analysis in a Chemical Industry - J. Nasl Seraji (Salāmat-i kār-i Īrān, 2008)
Background and aims   Prevention of potential accidents and safety promotion in chemical processes requires systematic safety management in them. The main objective of this study was analysis of important process equipment components failure modes and effects in H2S and CO2  isolation from extracted natural gas process.   Methods   This study was done in sweetening unit of an Iranian gas refinery. Failure Mode and Effect Analysis (FMEA) used for identification of process equipments failures.   Results   Totally 30 failures identified and evaluated using FMEA. P-1 blower's blade breaking and sour gas pressure control valve bearing tight moving had maximum risk Priority number (RPN), P-1 body corrosion and increasing plug lower side angle of reach DEAlevel control valve  in tower - 1 were minimum calculated RPN.   Conclusion   By providing a reliable documentation system for equipment failures and  incidents recording, maintaining of basic information for later safety assessments would be  possible. Also, the probability of failures and effects could be minimized by conducting preventive maintenance.